Estimation of postmortem interval by postmortem myocardial computed tomography value - Zhiyuan An (Journal of Forensic Science and Medicine, 2021)
Background: The estimation of postmortem interval (PMI) is one of the most important topics in forensic medicine research. We speculate that with an increased PMI, the computed tomography (CT) values of different tissues may show regular changes. Purpose: To use postmortem computed tomography (PMCT) to measure the myocardial CT value (unit: Hounsfield Unit, HU) of the heart to explore its pattern in postmortem change, and to discuss whether it can serve as a new parameter for PMI estimation. Methods: A total of 10 healthy adult New Zealand rabbits were selected and then put into a 20°C incubator after being sacrificed. Within 0–156 h after death, CT scans were performed every 12 h to detect changes in the myocardial CT value of the heart over time. Regression analysis was used to determine the relationship between the myocardial CT value of the heart and PMI. At the same time, HE and Masson were used to stain the cardiac tissue sections detected by PMCT at 0h, 48h and 156h, respectively. Results: During 0–156 h, the overall myocardial CT value showed a trend of first rising and then decreasing with the increase of PMI. The fitting regression equation was y = −2873.193 + 143.866x − 1.728x2 (x: myocardial CT value, unit: Hu; y: PMI, unit: h, R2 = 0.466, P < 0.05). During 48–156 h, the overall myocardial CT value decreased gradually with the increase of PMI. The fitting regression equation was y = −93.038 + 18.700x − 0.321x2 (x: myocardial CT value, unit: Hu; y: PMI, unit: h, R2 = 0.963, P < 0.001). The results of the morphological changes of the myocardial tissue structure after death showed that the myocardial cell structure was relatively complete at 0−48 hours after death; and the myocardial cell structure disappeared at 156 hours after death. Conclusions: Our results revealed evident postmortem changes in the myocardial CT value of the heart. Accordingly, measuring the myocardial CT value through PMCT shows promise for being used as a parameter for PMI estimation in forensic medicine and is worthy of further studies. The morphological changes of the myocardial tissue structure after death provide morphological basis for postmortem changes of tissue density, and further prove the reasons for the changes of CT value.